Diseño de un centro de salud comunitario utilizando criterios sostenibles para el sector de Petrillo - Rosero Choez, Allison Yamileth (2023)
Ecuador has a large deficit in hospital care, especially in rural sectors throughout the country, not only progressing economically, but putting the health of many inhabitants at risk, since to have medical attention or emergency they must move to another canton or city, which influences its economy and transportation. A study analysis was carried out whose purpose was to determine the lack of health equipment in the Petrillo commune, which resulted in the implementation of a health center in the sector being of great contribution, not only being Petrillo benefited, but also its surrounding areas, which allows optimizing a better quality of life for the population. Implementing larger and more pleasant spaces for the human being, applying sustainability criteria.